The barber of Seville - Sterbini, Cesare, 1784-1831.; Fisher, Burton D.; Sterbini, Cesare, 1784-1831.; Sterbini, Cesare, 1784-1831.; Rossini, Gioacchino, 1792-1868.; Beaumarchais, Pierre Augustin Caron de, 1732-1799. (Miami : Opera Journeys, 2005)
A comprehensive guide to Rossini's THE BARBER OF SEVILLE, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 35 music highlight examples.
The Barber of Seville/Opera Classics Library Series; Title Page; Contents; a Prelude; Provenance; Commentary and Analysis; Principal Characters in The Barber of Seville; Brief Story Synopsis; Story Narrative with Music Highlight Examples; Libretto; Discography; Videography; Dictionary of Opera and Musical Terms
Libretto by Cesare Sterbini.
Based on: Le Barbier de Séville / Pierre Augustin Caron de Beaumarchais.
Text in English; libretto in English and Italian.
Includes discography and videography.
eBooks on EBSCOhost
Keywords: Rossini, Gioacchino, -- 1792-1868.; Barbiere di Siviglia (Rossini, Gioacchino); Operas -- Librettos; Opéras -- Livrets; MUSIC -- Genres & Styles -- Opera; Operas -- Librettos